Leptopodidae (Insecta: Hemiptera: Heteroptera) of China: key, checklist, and new records - Wang, Yanhul; Chen, Pingping; Xie, Qiang (Zootaxa, 2026)
Four genera and nine species of Leptopodidae Brullé, 1836 are recorded from China, including one genus Erianotus Fieber, 1861 and four species Erianotus lanosus (Dufour, 1834), Leptopus travancorensis Distant, 1910, Patapius spinosus (Rossi, 1790), and Valleriola bui Li, Jin & Ye, 2023 now recorded from China for the first time. Photographs of the habitus and male genital capsules are provided. Additionally, a checklist of the family in China as well as an identification key to the species are presented. With the addition of the four newly recorded species, the distribution range of Leptopodidae in China has expanded from the Oriental Region to encompass both the Oriental and Palaearctic Regions.